2019
DOI: 10.1097/md.0000000000016905
|View full text |Cite
|
Sign up to set email alerts
|

Post percutaneous coronary interventional outcomes on proximal vs non-proximal lesions of the left and right coronary arteries

Abstract: Background:The prognosis of patients with coronary artery disease is mainly related to the extent of myocardium at risk. Proximal coronary arteries, especially the proximal left anterior descending coronary artery (LAD), supply a large part of the myocardium. In this analysis, we aimed to systematically compare the post percutaneous coronary interventional (PCI) outcomes observed with proximal vs non-proximal lesions of the left and right coronary arteries.Methods:MEDLARS Online, Excerpta Medica database, www.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…Even after treating patients with PPCI in minimal D2B time, medical treatment is still a cornerstone when treating patients after STEMI. In line with previous studies and current guidelines, beta blocker [27][28][29] and renin angiotensin aldosterone system inhibitors [30][31][32] treatment improved survival through the follow-up period.…”
Section: Discussionsupporting
confidence: 81%
“…Even after treating patients with PPCI in minimal D2B time, medical treatment is still a cornerstone when treating patients after STEMI. In line with previous studies and current guidelines, beta blocker [27][28][29] and renin angiotensin aldosterone system inhibitors [30][31][32] treatment improved survival through the follow-up period.…”
Section: Discussionsupporting
confidence: 81%
“…Also, mortality was higher in proximal LAD lesions compared to proximal RCA lesions that were percutaneously revascularized. 32 Coronary dominance has also been shown to influence the severity of coronary lesions and patient outcomes following percutaneous revascularization procedures. A study that enrolled 27,289 ACS patients reported that left coronary dominance was linked to an increased mortality rate over the course of 3.5 years after cardiac catheterization.…”
Section: Future Directionsmentioning
confidence: 99%
“…Nevertheless, these procedures might be associated with complications [ 9 , 10 , 11 ]. Furthermore, the problem at hand might not be fully addressed with the first intervention, often requiring repeat procedures [ 12 , 13 ]; with re-operative cardiac surgery in particular, there might be increased morbidity and mortality [ 14 ]. An additional therapeutic measure could thus present an appealing solution to facilitate tissue healing and regeneration after myocardial infarction (MI).…”
Section: Introductionmentioning
confidence: 99%